m6A RNA Methylation Regulators Contribute to Eutopic Endometrium and Myometrium Dysfunction in Adenomyosis - Zhai, Junyu; Li, Shang; Sen, Sushmita; Opoku-Anane, Jessica; Du, Yanzhi; Chen, Zi-Jiang; Giudice, Linda C. (Frontiers in Genetics, 2020)
Adenomyosis is a prevalent, estrogen-dependent uterine disorder wherein endometrial cells are abnormally present in the myometrium and are surrounded by hyperplastic/hypertrophic smooth muscle. Its etiology is unclear, although endometrial cell invasion into the myometrium has been postulated. RNA methylation, particularly N6-methyladenosine (m6A), plays an important role in regulating various physiological processes and invasive disorders. The goal of this in silico and lab-based experimental study was to explore a possible role for m6A in adenomyosis. Gene expression profiles of both the endometrium and myometrium of women with adenomyosis (cases) and without disease (controls) were obtained from the publicly available Gene Expression Omnibus (GEO) database. In the endometrium, STRING database analysis revealed that METTL3 functions as a “hub” gene of m6A methylation regulators, and the genes involved in m6A regulation, including METTL3, FTO, ZC3H13 and YTHDC1 expression, were significantly decreased in cases versus controls. Functional, co-expression and correlational analyses of endometrium from cases versus controls revealed decreased total m6A levels, induced by METTL3, and the downstream elevated insulin‐like growth factor‐1(IGF1) and D-Dopachrome Tautomerase (DDT), with the latter two having known functions in epithelial proliferation and cell migration, which are important processes in the pathogenesis of adenomyosis in endometrium. M6A methylation regulators, including RBM15/15B, ALKBH5, FTO, YTHDF1/2, KIAA1429, HNRNPC, METTL3, ZC3H13 and YTHDC2, were also differentially expressed in the myometrium from cases versus controls. We validated decreased total m6A levels and differential expression of m6A methylation regulators in the myometrium of patients with adenomyosis using qRT-PCR, immunohistochemistry and tissues available from our biorepository. Possible target genes, including cadherin 3(CDH), sodium channel β-subunit 4 (SCN4B) and placenta-specific protein 8 (PLAC8), which are involved in cell adhesion, muscle contraction and immune response in the myometrium of adenomyosis patients were also validate. Thus, through extensive public database mining and validation of select genes, this study, for the first time, implicates m6A and its methylation regulators in the pathogenesis of adenomyosis. Follow on functional studies are anticipated to elucidate mechanisms involving m6A and its regulators and down-stream effectors in the pathogenesis of this enigmatic reproductive disorder and potentially identify druggable targets to control its associated symptoms.